Molecular identification of a Fuegian dog belonging to the Fagnano Regional Museum ethnographic collection, Tierra del Fuego - Petrigh, Romina Sandra; Fugassa, Martín Horacio (Quaternary International)
Native-European contact in Tierra del Fuego was a rapid process, for which little ethnographic information has been produced. Although the Fuegian dog seemed to have been important to Selk'nam people's life, the taxonomic status of this extinct animal is still uncertain. The aim of the present work was to determine the zoological identity of a taxidermized canid belonging to a Fagnano Regional Museum collection, Río Grande, Tierra del Fuego. For this purpose, DNA from Fuegian dog and patagonian wild canids (Lycalopex culpaeus, Lycalopex griseus and Lycalopex gymnocercus) hairs was extracted. An mtDNA Region Control fragment was amplified by PCR and sequenced. Sequence alignment was performed among the sequences that were obtained in this research and the Canis lupus familiaris sequence from GenBank. Pairwise analysis showed a higher identity between the Fuegian dog and the culpeo fox (97.57%), with greater divergence with the current domestic dog (88.93%). These results were supported by the molecular phylogenetic analysis, suggesting atypical fox domestication by hunter-gatherers. Fil: Petrigh, Romina Sandra. Universidad Nacional de Mar del Plata; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata; Argentina Fil: Fugassa, Martín Horacio. Universidad Nacional de Mar del Plata; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata; Argentina